Celebrities and medical awareness—The case of celine dion and stiff-person syndrome - Elsalti, Abdulrahman; Darkhabani, Mohammad; Alrifaai, Mohamad Aosama; Mahroum, Naim (MDPI, 2023)
The positive role of celebrities in spreading important medical information and contributing to increasing public awareness regarding the diagnosis, treatment, and prevention of various medical conditions cannot be overemphasized. Interestingly and importantly at the same time, this impact is not related to the rarity of the disease, as very rare diseases are looked up by the public due to the fact that a celebrity suffers from this disorder. Therefore, if taken seriously and used to address the public in regard to critical medical conditions, such as screening for cancer or the importance of vaccines in fighting infections, celebrities could have a huge impact in this field. As previously shown in the medical literature, the recent announcement of the famous Canadian singer Celine Dion concerning her newly diagnosed stiff-person syndrome has influenced the public interest regarding the syndrome which manifested as an increased search volume related to the disorder as seen in Google Trends. In brief, in this short communication we aimed to address the phenomenon of celebrities’ impact on public apprehension, revise the syndrome for the medical community, and emphasize taking advantage of such involvement of celebrities for improving the spread of highly important medical information for the public.
Keywords: Stiff-Person Syndrome; Public Awareness; Celine Dion